PENGARUH ARAH AKSIAL TERHADAP SIFAT FISIKA BAMBU TUTUL (Bambusa maculata) di KABUPATEN LOMBOK TIMUR - Febriana Tri Wulandari (Lambung Mangkurat University-Indonesia, 2020)
Spotted bamboo was found in West Nusa Tenggara Province, especially in Eastern Lombok Regent. This bamboo has not been studied for its physical properties so that this study was aiming at identifying the physical properties of the bamboo. The information obtained from the study might be used by people for its appropriate utilization. The axial direction was investigated with the experimental method. This method investigated correlations among treated experiments [5]. The experiment design employed was complete random design (CRD) with the axial direction treatments: at the bottom, middle, and at the top portions with three replications. The statistical analyses were Anova with range tests at α = 5%, and Least Significant Difference (LSD) tests at α = 5%. The results showed that the treatments of physical properties (axial directions at the bottom, middle and top portions) were significantly different, except for the density of air-dried and oven-dried bamboo. The average of fresh moisture content was 73.73%, air-dried moisture content 12.56%; fresh volume density 0.68; air-dried volume density 0.80; oven-dried volume density 0.81.